1901 Del. Laws 408, § 16 - (:unkn) unknown (General Publisher, 1901)
Authorized the aldermen to extinguish and prevent bonfires in the streets, lanes, and alleys. The duty also included the suppression and preventing discharge of guns, pistols, firecrackers or fireworks in the town limits.
--
Keywords: DISCHARGE